Penyelesaian Tindak Pidana Kekerasan Dalam Rumah Tangga Yang Dilakukan Anggota TNI Di Lingkungan Pengadilan Militer II-10 Semarang - Wardhani, Ayu Larasati; , Kuswardani, S.H.,M.Hum (2017)
Target of this research is to know: 1) To know jurisdiction any kind of able to be imposed to member of TNI doing injustice hardness in household (KDRT); 2) For to description the process of solving to do an injustice of KDRT by member of TNI; and 3) For to description of the protection of law to do an injustice victim of KDRT by member of TNI. This research type is law of normative by using technique analyses data qualitative. Result of analysis indicate that 1) member of TNI doing an injustice hardness in household (KDRT) classified as collision of discipline, hence member of TNI the can fall the discipline sanction by superior master of rightful claimant punish (Ankum) then if in proven doing an injustice of the crime element is hereinafter finished to Military Jurisdiction; 2) Process the Solving of Injustice of KDRT by member of TNI, that is: investigation phase, phase delivery of case / prosecution, inspection phase in conference, and phase execution of decision; 3) Effort protection of victim of KDRT by member of TNI our relate at Republic of Indonesia Law Number 13 Year 2006 about Protection of Witness and Victim, and Law Number 23 Year 2004 about Abolition of Hardness In Household.